Combined Hamartoma of Retina and Retinal Pigment Epithelium Masquerade as Choroidal Melanoma in Young Patient - Amatya, Anupama; Tamang, Saksham; Sthapit, Purnima Rajkarnikar (Nepalese Journal of Ophthalmology, 2026)
Introduction: Combined hamartoma of retina and retinal pigment epithelium is a rare benign ocular tumour resultingfrom abnormal proliferation of glial cells, vascular tissue and pigment epithelial cellsCase: A 29-year-old male presented with complaint of diminution of vision in his right eye, noticed incidentallyduring screening.Observation: On examination, a flat, unilateral, solitary, greyish brown peri-papillary lesion with irregularlypigmented border with an epiretinal membrane in right eye. The Optical Coherence Tomography showed a thickenedretina with disorganisation of retinal layers, a hyper-reflective inner retinal layer with fine retinal traction peaks, andpresence of an epiretinal membrane. Histopathological examination was not done.Conclusion: Combined hamartoma of retina and retinal pigment epithelium is a rare benign tumour. Proper diagnosisis important as it can be confused with more severe pathologies like choroidal melanoma, Retinal pigment epitheliumadenocarcinoma.